Yoruba ethnic nationalism, power elite politics and the Nigerian state, 1948–2007. Issue 2 (3rd April 2017) - Adesoji, Abimbola O.
Abstract: Known for its political sophistication, the Yoruba remain a force in Nigerian Politics. But its political peculiarities have remained more of an albatross driving a wedge within the group and limiting its political influence in a highly competitive ethno-regional and religious inclined Nigerian polity. These peculiarities have distinguished the Yoruba and its brand of nationalism. But they have also given a contradictory perception of its ideology and philosophy on one hand and its leadership on the other hand. Using its acclaimed but seriously constrained Yoruba homogeneity as a basis, this paper argues that the inability of the elite to distinguish their intent or person from the collective good of the group has proved disastrous. The paper concludes that Yoruba nationalism has suffered serious reversals since the attainment of political independence with the seemingly unending acrimonious struggle for power and its attendant benefits. The paper suggests a re-definition and a re-alignment of ideology, leadership and people's interest, without which the idea of Yoruba nationalism will be more of noise without substance and effect either within the group or in the larger Nigerian state.